PENGEMBANGAN MODUL KIMIA BERBASIS DISCOVERY LEARNING PADA MATERI LARUTAN PENYANGGA KELAS XI - Wahdah Aliyah; Rody Putra Sartika; Rahmat Rasmawan; Hairida Hairida; Masriani Masriani (Jurnal Education and Development, 2023)
This study aims to determine the feasibility and teacher's response to the chemistry module based on discovery learning on buffer solution material. This research method is research and development (R&D) using the ADDIE development model. However, in this study the researchers only limited it to AAD (analysis, design, development). Discovery learning based chemistry module on buffer solution material is the subject of this research. Data collection techniques used are measurement techniques, direct and indirect communication techniques. The results of the feasibility test showed that the chemistry module based on discovery learning which was developed obtained a percentage of 93% from the content aspect, 98% from the presentation aspect, 91% from the language aspect, and 86% from the graphic aspect. Based on these results it can be concluded that the chemistry module based on discovery learning on buffer solution material is suitable for use in chemistry learning with an average feasibility of 93% and a teacher response of 97%. These results indicate that the chemistry module based on discovery learning on buffer solution material can be used for chemistry learning in schools.